THE ROLE OF NGOS IN POVERTY REDUCTION: EXAMINING THE EFFECTIVENESS OF UMMAH WELFARE TRUST’S PROGRAM IN SIERRA LEONE - Jalloh, Mohamed Baillor; Nyeleker, Kerkulah P (Journal of Social Politics and Governance (JSPG), 2025)
In recent years, NGOs have emerged as important institutions assisting governments, especially in poverty reduction. While many studies have focused on NGOs' roles in social welfare, this study examines the role of NGOs in poverty reduction by evaluating the effectiveness of the Ummah Welfare Trust (UWT) program in reducing extreme poverty in Sierra Leone. We employed a qualitative research approach, gathering data from in-depth interviews, peer-reviewed journals, reports, and online resources. We analyzed the data interactively using NVivo 12 Plus software, based by Richard M. Steers' effectiveness theory across three dimensions: integration, adaptation, and goal attainment. Our findings reveal that: (1) Integration – UWT has effectively woven its poverty alleviation program by managing policy outreach and enhancing communication while fostering public consensus. (2) Adaptation – UWT has refined its strategies through capacity building by localizing its programs to address the local community's needs. Lastly, (3) Goal attainment – although UWT is yet to achieve its objectives, it has significantly impacted extreme poverty reduction in Sierra Leone, with the rate decreasing from 26.6% in 2020 to 24.5% in 2024. This study offers evidence of how NGOs contribute to poverty reduction, highlighting their essential role in supporting governments’ efforts in nation building.